Sports Activities Of A Entertaining Nature And Their Impact On Some Of The Life Skills Among Primary School Pupils From The Point Of View Of Their Teachers - Nadour, Aissa; Messahli, Seghir (sports creativity, 2025)
This study aimed to see how entertaining sports activities reflect some life skills (self-confidence, communication) among primary school pupils from the point of view of their teachers through our observation of the extent to which these activities are reflected and effective in the different aspects of individuals’ personality. The study was conducted on a sample of 80 teachers at the primary schools of Hassi Delaa -(Laghouat) For the academic year2019-2020 To achieve the objectives of the study, the descriptive method was used by distributing the questionnaire forms to the sample population, and to analyze and interpret the results, a set of statistical tools were used such as: percentage, chi² test . The two most important results are: Sports activities of a entertaining nature have a positive impact on the development of the life skills mentioned above, so the researchers recommend that this kind of activity be taken into consideration, especially in this age range And exploit it in the field